TOC and TPH Relationships in Khor Al-Zubair Sediments: Hubungan TOC dan TPH dalam Sedimen Khor Al-Zubair - Fatima Fakhir Abo-Turab; Abbas Hameed Mohammed; Hamid Talib Al-Saad (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Total petroleum hydrocarbons are persistent contaminants in marine sediments and are closely associated with organic matter. Specific Background Total organic carbon is widely used as an indicator of sedimentary processes and hydrocarbon retention. Knowledge Gap However, limited studies have evaluated the vertical and spatial relationship between TOC and TPHs in sediment cores from Khor Al-Zubair. Aims This study aimed to determine the distribution of TOC and TPHs and assess their relationship in sediment cores collected from five stations in Khor Al-Zubair, southern Iraq. Results TOC values ranged from 0.058% to 0.193%, while TPH concentrations ranged from 0.2894 to 12.4434 µg/g, with higher values generally recorded in surface layers and at Station 5. Correlation analysis revealed variable relationships between TOC and TPHs, including strong positive correlations at most stations and a strong negative correlation at one station. Novelty This study provides station-specific insights into contrasting TOC–TPH relationships within a single lagoon system. Implications The findings highlight the role of organic matter and local environmental conditions in controlling hydrocarbon distribution and support the use of TOC as an indicator of sedimentary hydrocarbon retention. Keywords: Total Petroleum Hydrocarbons, Total Organic Carbon, Sediment Cores, Khor Al-Zubair, Marine Pollution Key Findings Highlights: Concentrations varied vertically with higher values near sediment surfaces. Organic matter showed contrasting associations across sampling locations. Spatial patterns reflected localized anthropogenic activities.